2006
DOI: 10.1051/jp4:2006132057
|View full text |Cite
|
Sign up to set email alerts
|

Growth of long range ordered pentacene/benzenethiol/Cu(100) heterostructure

Abstract: We present a method of producing a long-range ordered pentacene ultra-thin film on a benzenethiol organic buffer layer at saturation coverage, deposited on a cleaned. single crystalline Cu(100) surface, by means of ultra-high-vacuum organic molecular beam epitaxy. The growth morphology is investigated using in-situ low-energy electron-diffraction (LEED) and high-resolution UV photoelectron spectroscopy (HR-UPS). The change in Surface symmetry from c(4x4) at low coverage to c(2 x 6)/c(2 x 2) at saturation cover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 0 publications
1
7
0
Order By: Relevance
“…11,12,26 Exposures inside the prechamber were done with a constant rate of 0.3-0.5 L / min ͑1 L = 1.33ϫ 10 −6 mbar s͒ at room temperature ͑RT͒, maintaining the pressure at 2 ϫ 10 −8 mbar, so that the saturation coverage was reached by exposing to about 33 L. Under these conditions, the RHEED pattern revealed a c͑2 ϫ 6͒ two-domain saturation phase, in agreement with previous results. 11,12,26 Pentacene was thermally evaporated in situ by organic molecular beam deposition from a resistively heated quartz crucible. The evaporation rate, calibrated by a quartz microbalance, was kept constant during each deposition at a few Å/min.…”
Section: Methodssupporting
confidence: 89%
See 3 more Smart Citations
“…11,12,26 Exposures inside the prechamber were done with a constant rate of 0.3-0.5 L / min ͑1 L = 1.33ϫ 10 −6 mbar s͒ at room temperature ͑RT͒, maintaining the pressure at 2 ϫ 10 −8 mbar, so that the saturation coverage was reached by exposing to about 33 L. Under these conditions, the RHEED pattern revealed a c͑2 ϫ 6͒ two-domain saturation phase, in agreement with previous results. 11,12,26 Pentacene was thermally evaporated in situ by organic molecular beam deposition from a resistively heated quartz crucible. The evaporation rate, calibrated by a quartz microbalance, was kept constant during each deposition at a few Å/min.…”
Section: Methodssupporting
confidence: 89%
“…The pentacene standing-up molecules in the single layer on the Bt-SAM layer are packed with a tilt angle consistent with previous results obtained for pentacene deposited on SAM buffer layers and on inert substrates. [11][12][13]34 The same fitting procedure has been employed for the pentacene/Cu͑119͒ interface, where the overall polarization dependence of the NEXAFS data is reversed with respect to the pentacene/Bt-SAM heterostructure, as shown in the right-bottom panel of Fig. 3.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this work, we demonstrate the use of an interfacial organic layer (IOL) to passivate chemical decomposition of thiophenes and carboxylic acids (Scheme ) at the Cu(001) surface, while also achieving formation of a crystalline layer of the functional molecules on top of the IOL at room temperature. Crystalline ordering in multilayered structures has been reported in single-component systems as well as multicomponent systems (some studied only at cryogenic temperatures). However, in those prior studies atomically precise ordering was not reported for chemically fragile species, i.e., those that would decompose if deposited directly on the metal surface.…”
Section: Introductionmentioning
confidence: 99%